On the demand for grandchildren: Tied transfers and the demonstration effect - Donald Cox; Oded Stark (Institute for Advanced Studies (IHS), 2004)
Most private giving between living generations takes the form of tied transfers, such as help with housing downpayments. We argue that parents provide help with downpayments in order to encourage the production of grandchildren, and that such a subsidization emanates from the demonstration effect: a child's propensity to furnish parents with attention and care can be conditioned by parental example. Parents who desire such transfers in the future have an incentive to make transfers to their own parents in order to instill appropriate preferences in their children. This generates a derived demand for grandchildren since potential grandparents will be treated better by their adult children if the latter have their own children to whom to demonstrate the appropriate behavior. Empirical work, based on waves 1 and 2 of the National Survey of Families and Households, indicates behavior consistent with subsidization of the production of grandchildren and the demonstration effect.
Keywords: A14; D10; I30; J13; J14; 330; intergenerational transfers; the demonstration effect; inculcating values in children; subsidizing the production of grandchildren; housing downpayments; Generationenbeziehungen; Kinder; Familienökonomik; Wohnungsbaufinanzierung; Privater Transfer; Konsuminterdependenz; Schätzung; Theorie; USA; Eltern